Applications of light-responsive systems for cancer theranostics - Chen, Hongzhong (2020)
Achieving controlled and targeted delivery of chemotherapeutic drugs and other therapeutic agents to tumor sites is challenging. Among many stimulus strategies, light as a mode of action shows various advantages such as high spatiotemporal selectivity, minimal invasiveness and easy operation. Thus, drug delivery systems (DDSs) have been designed with the incorporation of various functionalities responsive to light as an exogenous stimulus. Early development has focused on guiding chemotherapeutic drugs to designated location, followed by the utilization of UV irradiation for controlled drug release. Because of the disadvantages of UV light such as phototoxicity and limited tissue penetration depth, scientists have moved the research focus onto developing nanoparticle systems responsive to light in the visible region (400–700 nm), aiming to reduce the phototoxicity. In order to enhance the tissue penetration depth, near-infrared light triggered DDSs become increasingly important. In addition, light-based advanced systems for fluorescent and photoacoustic imaging, as well as photodynamic and photothermal therapy have also been reported. Herein, we highlight some of recent developments by applying light-responsive systems in cancer theranostics, including light activated drug release, photodynamic and photothermal therapy, and bioimaging techniques such as fluorescent and photoacoustic imaging. Future prospect of light-mediated cancer treatment is discussed at the end of the review. This Spotlights on Applications article aims to provide up-to-date information about the rapidly developing field of light-based cancer theranostics.